The normative ethics of immigration detention in liberal states - Silverman, S; Silverman, Stephanie Jessica (2013)
This thesis explores the normative propriety of immigration detention in liberal states. In the first part of the thesis, I explore the development, current practice, and popular justifications for immigration detention in the United Kingdom. I argue that a crucial but unacknowledged role for immigration detention is to function as a political spectacle of the centralisation of power in liberal states. I find that the key motivation for detaining non-citizens is that they could abscond before their removals. I conclude that this basis for detention is normatively acceptable in only very limited cases and, even then, alternatives are often available and ethically preferable. Based on the fact that there is a normatively acceptable rationale, albeit circumscribed, for detention practices, I then propose a framework of minimum standards of treatment in detention that I advise all liberal states to follow. After outlining my proposal, I turn in the second part of the thesis to an examination of the normative theories of immigration control and how they take account of detention. Normative theorists differ in how they balance their commitments to individual and state rights, yet I find the majority concedes the need for some degree of immigration admissions control. Such theories face a moral dilemma: there can be no immigration control without detention, and so detention becomes an implicit assumption for these normative theories to be coherent. A potential solution for combating the practical problems associated with the growing, worsening detention estates as well as the moral dilemma of incarcerating a non-citizen based on fear of absconding would be to open borders and eliminate immigration control. Given the reality of the sovereign right to control immigration, however, I argue that the more feasible normative answer is lobby liberal states to adopt my framework of minimum standards of treatment while simultaneously pressing for open borders as the long-term ethical goal.